Flavonoid-derived anisotropic silver nanoparticles inhibit growth and change the expression of virulence genes in Escherichia coli SM10. Issue 9 (25th January 2018) - Osonga, Francis J.; Akgul, Ali; Yazgan, Idris; Akgul, Ayfer; Ontman, Renata; Kariuki, Victor M.; Eshun, Gaddi B.; Sadik, Omowunmi A.
Abstract : We hereby present a novel greener and ecofriendly synthesis of anisotropic silver nanoparticles (AgNPs) using water soluble quercetin diphosphate (QDP). QDP was employed as a reducing, capping and stabilizing agent at room temperature without any extraneous reagents. Abstract : We hereby present a novel greener and ecofriendly synthesis of anisotropic silver nanoparticles (AgNPs) using water soluble quercetin diphosphate (QDP). QDP was employed as a reducing, capping and stabilizing agent at room temperature without any extraneous reagents. The purpose of this study was to determine the effects of modified quercetin pentaphosphate silver nanoparticles (QPP-AgNPs) and quercetin diphosphate derived silver nanoparticles (QDP-AgNPs) on microbial growth and expressions of virulence-related genes in Escherichia coli SM10. The gene expression analysis was carried out for 12 genes which are related to virulence and stress in E. coli SM10, namely: RpoD, RpoS, ibpB, clpB, uspA, fliC, fimH, fimF, kdpE, artJ, hyaA, and gyrA. Results showed that QDP-AgNPs reduced the swarming motility by 98% which correlated with the reduction in the expression of FliC flagellar gene. A simultaneous increase in the expression of the fimbrial genes FimH and FimF that are related to motility was recorded. In contrast, treatment of the microbes with QPP-AgNPs resulted in 90% of the swarming motility at different patterns compared to QDP-AgNPs treatment for the gene expressions of motility elements. The study revealed that QDP-AgNPs up-regulated the stress related RpoD and ibpB expressions, while QPP-AgNPs up-regulated the stress related RpoS and uspA gene expressions. However, both QDP-AgNPs and QPP-AgNPs up-regulated kpdE, artJ and gry at different levels. QDP-AgNPs were also tested for their antibacterial and antifungal activities, which showed μmolar cidal activity. The growth kinetics of both Gram (−) and Gram (+) bacteria were strongly altered by QDP-AgNPs activity. Energy dispersive absorption spectroscopy (EDS) studies revealed that silver ions and/or the nanoparticles themselves transferred into bacterial cells. To the best of our knowledge, this is the first report of studying the genetic and kinetic response of bacteria to modified quercetin phosphate mediated silver nanoparticles and we hereby report that the molecules used to synthesize AgNPs bring about a strong effect on AgNPs manipulatory activity on the tested 12-genes.